Relationship between engagement with the impossible task, cognitive testing, and cognitive questionnaires in a population of aging dogs - Khan, Michael Z.; Mondino, Alejandra; Russell, Katharine; Case, Beth; Fefer, Gilad; Woods, Hope; Olby, Natasha J.; Gruen, Margaret E. (Frontiers in Veterinary Science, 2023)
The aim of this study was to evaluate the engagement of aging dogs with a cognitively challenging and potentially frustrating task (the impossible task). Based on previous observations, we predicted that dogs showing signs of cognitive impairment in other cognitive tests and owner-completed questionnaires would show reduced engagement with the task. In this task, dogs were shown a piece of food in a clear container that they could not open; time spent interacting with the container and the experimenter were measured. While the impossible task has not been used as a measure of frustration, the parameters of the test design create a potential frustrative state, making this assessment appropriate. Thirty-two dogs enrolled in a longitudinal aging study participated in the study. Owners were asked to complete two cognitive dysfunction screening questionnaires (Canine Dementia Scale [CADES] and Canine Cognitive Dysfunction Rating Scale [CCDR]) as well a questionnaire assessing general frustration. Dogs participated in multiple measures of cognitive function as well the impossible task. Latency to disengage from the impossible task was faster for dogs with higher total (more impaired) CADES (p=0.02) and total CCDR (p=0.04) scores. Latency to disengage also correlated with decreased performance in cognitive tests observing social cues (p=0.01 ), working memory (p=<0.001), spatial reasoning and reversal learning (p=0.02), and sustained attention (p=0.02). The high correlation with several cognitive measures and the ease of administration of this test makes it a useful tool in evaluating canine cognitive dysfunction syndrome, however it is unclear if increased frustration or other cognitive processes are contributing to the observed changes.